INFLUENCE OF PARENTAL INVOLVEMENT ON LEARNING OUTCOMES AMONG PRESCHOOL LEARNERS IN MBOONI EAST SUB COUNTY, MAKUENI COUNTY - MWANIA, JUDITH M. (My University, 2019)
The purpose of this study was to investigate the influence of parental involvement on children’s learning outcomes among preschool learners in Mbooni Sub County, Makueni County. Three research objectives guided the study. The first research objective aimed at determining the extent to which parental involvement in activities at school affect the learning outcomes. Secondly, the study assessed parental literacy level on involvement in children’s learning styles on their learning outcomes as well as examined the parental home activities on learning outcomes of children. This study was guided by Social Learning theory developed by Lev Vygosky and Epstein’s six types of Parental Involvement framework theory, that explain the role and involvement of parents in children’s education. The study adopted a descriptive survey design since the design use structured interviews and questionnaire that intended to verify information, perceptions, opinions and views of the respondents and an observation schedule for collecting data on the learning outcomes of the children. Purposive sampling was used to select the teachers and parents whereas simple random sampling was used to select learners. A sample of 42 teachers, 33 parents and 72 ECDE learners were involved. Validity of the instruments was tested during piloting. Reliability of the instruments was ascertained through testing and re-testing to 2 parents, 2 preschool teachers and 2 public preschools that did not form the sampled for the actual study. Data was collected after acquiring permit from NACOSTI. Instructions and arrangements on how to collect the data was made with regard to dates agreed between the researcher and the respondents on when to deliver the questionnaire and observe the children during live lessons as well as conducting of the interviews. Data were analyzed using both qualitative and quantitative techniques. Thematic analysis was used to analyze qualitative data along the specific objectives and presentation was in narrative forms. Descriptive analysis was used to analyze quantitative data with the use of Statistical Packages for Social Sciences (SPSS Version 23) in frequencies and percentages and presented using tables, pie charts, and graphs. The study has established that parents’ involvement in children’s education through participating in school activities and homebased learning activities contributes to holistic on learning outcomes. The study also established that the more the parents’ involvement in children’s literacy activities, the better the learning outcomes. The study thus recommends that parents need to provide conducive environment where learning activities are designed to promote learning outcomes among learners. The Ministry of Education and policy-makers should revise the pre-primary school curriculum to incorporate more parental activities geared towards enhancing attainment of basic skills among preschool children. Key stakeholders in the education industry may benefit from the study, for example, curriculum developers may be motivated to develop more interactive materials such as books and play materials which parents can effectively use with their children and may encourage parents to put forth extra effort to become more involved in their preschooler’s education. This study may inform parents and policy makers on the influence of parental involvement on children’s learning outcomes in Mbooni East Sub County. Preschool learners learning outcomes may improve through the early intervention and involvement of their parents in their education.